Kemampuan Gliocladium sp. Akk-1 dalam Memproduksi Antifungi Pada - Arifin, Yusmanidar (Jurnal Embrio, 2008)
The aim of this research is to find out the interaction between incubation period and type of fermentation medium wich showing the highest antifungal activity. The method was experimental with a Completely Randomized Design (CRD) constructed in factorial pattern. The experiment had two factors i.e. : type of fermentation medium consisted of three level i.e. : Potato Dextrose Broth (PDB), Gliotoxin Fermentation Medium (GFM) and Raulin Thom Medium (RTM). The incubation period consisted of three level i.e. : 6, 12 and 18 days. Ampunt of treatment combination were 3 X 3 = 9, showing an inter-factor level combination. Every treatmant had 3 replicates. The overall treatment consisted of 27 treatment units for R. solani and 27 treatment units for Pythium sp. The observed variables were percentage on the antifungal compounds towards the pathogen’s growth, biomass dry weight of Gliocladium sp. Akk-1 and medium pH before and after fermentation. The result showed that Gliocladium sp. Akk-1 was able to produce antifungal compounds in every treatmant. The ability shown by inhibition activity toward the pathogens R. solani and Pythium sp. The highest inhibition activity shown by the interaction treatment between RTM and 6-day incubation period i.e. : 55.70% towards Pythium sp. It can be conclude thet RTM is more appropriate for Gliocladium sp. Akk-1 to produce antifungal compounds with havesting period of 6-12 days.